The prototype HIV-1 maturation inhibitor, bevirimat, binds to the CA-SP1 cleavage site in immature Gag particles - Nguyen, Albert T (BioMed Central, 2011)
BACKGROUND: Bevirimat, the prototype Human Immunodeficiency Virus type 1 (HIV-1) maturation inhibitor, is highly potent in cell culture and efficacious in HIV-1 infected patients. In contrast to inhibitors that target the active site of the viral protease, bevirimat specifically inhibits a single cleavage event, the final processing step for the Gag precursor where p25 (CA-SP1) is cleaved to p24 (CA) and SP1. RESULTS: In this study, photoaffinity analogs of bevirimat and mass spectrometry were employed to map the binding site of bevirimat to Gag within immature virus-like particles. Bevirimat analogs were found to crosslink to sequences overlapping, or proximal to, the CA-SP1 cleavage site, consistent with previous biochemical data on the effect of bevirimat on Gag processing and with genetic data from resistance mutations, in a region predicted by NMR and mutational studies to have α-helical character. Unexpectedly, a second region of interaction was found within the Major Homology Region (MHR). Extensive prior genetic evidence suggests that the MHR is critical for virus assembly. CONCLUSIONS: This is the first demonstration of a direct interaction between the maturation inhibitor, bevirimat, and its target, Gag. Information gained from this study sheds light on the mechanisms by which the virus develops resistance to this class of drug and may aid in the design of next-generation maturation inhibitors.